AN ANALYSIS OF IMPORTANT POLICIES FOR ACCELERATING DEVELOPMENT IN NEPAL - Sudarshan Neupane (Diponegoro University, 2015)
Nepal belongs to one of the least developed countries around the world with HDI 157 out of 187 countries (UNDP 2013). Even though poverty in Nepal has reduced to 24.8% in the latest census, the livelihoods of the poorest people living in the remote communities are still vulnerable. Two third of the population still depends on the subsistence agriculture. Similarly, due to lack of job opportunities, youth migration is escalating and Nepal is facing one of the most critical phases of development in its history (Snellinger 2009). Inadequate infrastructure and poor road connectivity are other constraints for the development (World Bank 2011). It follows that, poor access to electricity is another challenge despite the country’s enormous potential for hydroelectricity. Similarly, Nepal has huge prospective for tourism due to its unique natural resources (Bhandari 2004). Nonetheless, Nepal has not benefited optimally from the tourism sector for its self-sustained development. Recently Government of Nepal (2011) has announced diverse policies for accelerating development through proper utilization of local resources. This paper critically evaluates the crucial policies such as Agriculture Development Strategy, National Cooperatives Policy, National Youth Policy, and Micro-hydro for Rural Development, and Tourism for Development. The paper discusses each of these policies’ background; critically analyse the likelihood as well as challenges for fast-tracking development; and finally offers some recommendations based discussion and analysis.